Ubiquitous metal, Difficult to track: Towards an understanding of the regulation of Titanium(IV) in humans - Loza Rosas, Sergio A. (Metallomics, 2017)
Despite the ubiquitous nature of titanium(IV) and several examples of its beneficial behavior in different organisms, the metal remains underappreciated in biology. There is little understanding of how the metal might play an important function in the human body. Nonetheless, new insight is obtained regarding the molecular mechanisms that regulate the blood speciation of the metal to maintain it in nontoxic and potentially bioavailable form for use in the body. This review surveys the literature on Ti(IV) application in prosthetics and in the development of anticancer therapeutics to gain insight into soluble Ti(IV) influx in the body and its long-term impact. The limitation in analytical tools makes it difficult to depict the full picture of how Ti(IV) is transported and distributed throughout the body. Improved understanding of Ti function and its interaction with biomolecules will be helpful in developing future technologies for its imaging in the body.